Age - Krisniawati, Nia; Ciptaningtyas, Vincentia Rizke; Reki, Winarto (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Most blood culture contaminants are coagulase-negative staphylococci (CoNS), which are also the leading cause of nosocomial bloodstream infections. To date, no research in Indonesia has analyzed the potential causes of a CoNS infection in the bloodstream. The goal of this research was to better understand who is at risk for developing a CONS-related bloodstream infection while in a hospital setting. Secondary data from the CONS blood culture results at Dr. Kariadi Hospital Semarang were used in this retrospective cross-sectional study conducted between January 1 and December 31, 2016. The Vitek-2 Compact System (Biomerieux, USA) and the Kirby Bauer method (Clinical & Laboratory Standards Institute (CLSI) of the USA) were used for the antibiotic identification and sensitivity testing, respectively. Multivariate with multiple logistic regressions and the Chi-Square test for categorical variables were used in the analysis. Among the study's 272 participants, 158 (58.1%) developed CONS-related bloodstream infections. Risk factors for central nervous system (CNS) bloodstream infection in 18-year-olds include preterm birth, low birth weight (LBW), compromised immunity, malnutrition, immunosuppressive therapy, and peripheral intravenous use. Age >=18, malnutrition, and immunosuppression therapy all ranked high as risk factors in a multivariate analysis. Risk factors for CONS-causing bloodstream infections in people aged 18 include malnutrition and immunosuppressant therapy.